Prophages and past prophage-host interactions revealed by CRISPR spacer content in a fish pathogen - Laanto, Elina; Ravantti, Janne; Sundberg, Lotta-Riina (Microorganisms, 2020)
The role of prophages in the evolution, diversification, or virulence of the fish pathogen Flavobacterium columnare has not been studied thus far. Here, we describe a functional spontaneously inducing prophage fF4 from the F. columnare type strain ATCC 23463, which is not detectable with commonly used prophage search methods. We show that this prophage type has a global distribution and is present in strains isolated from Finland, Thailand, Japan, and North America. The virions of fF4 are myoviruses with contractile tails and infect only bacterial strains originating from Northern Finland. The fF4 resembles transposable phages by similar genome organization and several gene orthologs. Additional bioinformatic analyses reveal several species in the phylum Bacteroidetes that host a similar type of putative prophage, including bacteria that are important animal and human pathogens. Furthermore, a survey of F. columnare Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) spacers indicate a shared evolutionary history between F. columnare strains and the fF4 phage, and another putative prophage in the F. columnare strain ATCC 49512, named p49512. First, CRISPR spacer content from the two CRISPR loci (types II-C and VI-B) of the fF4 lysogen F. columnare ATCC 23463 revealed a phage terminase protein-matching spacer in the VI-B locus. This spacer is also present in two Chinese F. columnare strains. Second, CRISPR analysis revealed four F. columnare strains that contain unique spacers targeting different regions of the putative prophage p49512 in the F. columnare strain ATCC 49512, despite the geographical distance or genomovar of the different strains. This suggests a common ancestry for the F. columnare prophages and different host strains. Peer reviewed